Marine protected areas, Satoumi, and territorial use rights for fisheries: A case study from hinase, Japan. (May 2018) - Tsurita, Izumi; Hori, Juri; Kunieda, Toshihiro; Hori, Masakazu; Makino, Mitsutaku
Abstract: In spite of the growing attention towards the overall quality of Marine Protected Areas (MPAs), most empirical studies so far have narrowly focused their assessments on specific natural or social features and governing structures. In response, this study analyzed multi-use MPAs in the eelgrass restoration site in Hinase, Okayama, Japan in their environmental, economic and social dimensions. Considering changes in time and space as well as internal and external influences, the study faced many difficulties in dealing with the dynamics of MPA environments. At the same time, it showed clearly the control over development and fishery activities by several MPA relevant regulations, improvements of the ecological function by the regrowth of eelgrass, an increase in some fish species due to the same regrowth, and expansion of social networks deriving from the restoration activity. The study also revealed convincing evidence that self-motivated MPA management practice by fishers under the Territorial Use Rights for Fisheries (TURFs), in conjunction with other mixed management systems such as Satoumi, could lead to flexible and long-term efforts for improving food security, livelihoods, and the marine environment. This study highlights the importance of comprehensive research to deepen the understanding of the structure and functions of complex and diverse marine ecosystems and social systems. Highlights: MPAs have been assessed mainly under a specific scientific field or administrative body so far. This study on multi-use MPAs at the eelgrass restoration site in Japan attempted to move beyond these parameters. The study revealed a control on development and fishery activities by several MPA related regulations. It also showed an improvement of ecological functions bringing an increase in some fish species by the eelgrass regrowth. Finally, it confirmed an expansion of social networks associated with the systems of MPAs, Satoumi, and TURFs.